Vegetational Structures and Species Diversity in Tropical Dry Deciduous Forest of Uttar Pradesh, India - Verma, M. K.; Niranjan, R. K.; Pal, Amit (Indian Forester, 2015)
The forests of Lalitpur district of Bundelkhand region of Uttar Pradesh, India have been undertaken for phytosociological attributes of the forest community. The survey documentation of the plant species in the different forests areas recorded 59 species of tree and 40 species of shrubs/herbs/climbers. The dominant tree species Butea monosperma exhibited higher IVI value (21.87) and among shrub/herb/climber species Flacourtia indica exhibited 2 higher IVI value (62.13). The basal area of different tree species varied between 6.7029 to 0.0039 m2/ha where Butea monosperma showed maximum density among the trees and the basal area of different shrub/herb/climber species varied between 0.4329 to 0.0006 m2/ha where Zizyphus mauritiana showed maximum density. The species diversity (H’), equitability (E) and concentration of dominance (D) have been recorded as 3.65, 0.89 and 0.97 for tree species whereas 3.20, 0.87 and 0.93 for lower group of plants respectively.